Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

2. Efectuar:

[tex]c = \sqrt{(x-5)^2 - (x+3)^2 + 16x}[/tex]

A. 1
B. 2
C. 3
D. 4
E. 5


Sagot :

Let’s evaluate the expression [tex]\( c = \sqrt{(x-5)^2-(x+3)^2+16x} \)[/tex] step by step.

1. Expand the squared terms:
- [tex]\((x-5)^2 = x^2 - 10x + 25\)[/tex]
- [tex]\((x+3)^2 = x^2 + 6x + 9\)[/tex]

2. Substitute these expansions into the given expression:
[tex]\[ c = \sqrt{(x^2 - 10x + 25) - (x^2 + 6x + 9) + 16x} \][/tex]

3. Combine like terms inside the square root:
- Distribute the subtraction over the terms:
[tex]\[ (x^2 - 10x + 25) - (x^2 + 6x + 9) = x^2 - 10x + 25 - x^2 - 6x - 9 \][/tex]
- Simplify the expression:
[tex]\[ = x^2 - x^2 - 10x - 6x + 25 - 9 \][/tex]
[tex]\[ = -16x + 16 \][/tex]
- Don’t forget to add the [tex]\(16x\)[/tex] from the original problem:
[tex]\[ -16x + 16 + 16x = 16 \][/tex]

4. Simplify inside the square root:
[tex]\[ c = \sqrt{16} \][/tex]

5. Compute the square root:
[tex]\[ c = 4 \][/tex]

So, the simplified result is [tex]\( c = 4 \)[/tex].

Thus, the correct answer is:
[tex]\[ \boxed{4} \][/tex]